2014
DOI: 10.3857/roj.2014.32.3.163
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of stereotactic body radiotherapy for unresectable primary or recurrent cholangiocarcinoma

Abstract: PurposeTo report the results of stereotactic body radiotherapy (SBRT) for unresectable primary or recurrent cholangiocarcinoma.Materials and MethodsFrom January 2005 through August 2013, 58 patients with unresectable primary (n = 28) or recurrent (n = 30) cholangiocarcinoma treated by SBRT were retrospectively analyzed. The median prescribed dose was 45 Gy in 3 fractions (range, 15 to 60 Gy in 1-5 fractions). Patients were treated by SBRT only (n = 53) or EBRT + SBRT boost (n = 5). The median tumor volume was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 17 publications
3
77
1
Order By: Relevance
“…Similar to the patients in our study, treatment margins of approximately 5 mm were used. The third study was a larger series that was published in 2014 and included 58 patients (half with primary tumors and half with recurrent disease) who were treated with SBRT 19 . The rates of local control at 1- and 2-year follow-up were 85% and 72%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the patients in our study, treatment margins of approximately 5 mm were used. The third study was a larger series that was published in 2014 and included 58 patients (half with primary tumors and half with recurrent disease) who were treated with SBRT 19 . The rates of local control at 1- and 2-year follow-up were 85% and 72%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for its use in cholangiocarcinoma is restricted to retrospective single institution studies. Jung et al reported outcomes in patients with unresectable primary or recurrent postoperative intrahepatic cholangiocarcinoma treated with SBRT (n = 53) or conventional EBRT plus SBRT boost (n = 5) and found a median OS of 10 months [81]. Grade I/II complications occurred in 29% and grade III/IV complications in 10% with one mortality from gastric perforation.…”
Section: Radiation Oncological Therapiesmentioning
confidence: 99%
“…Small studies have shown good local disease control and potential survival benefit of SBRT alone or combined with EBRT for unresectable and recurrent CC. 136,137 To minimize the radiation-induced toxicity, treatment with proton beams has been suggested. A recent study demonstrated that after percutaneous implantation of fiducial markers for localization, proton beam therapy was associated with an increased median survival compared to palliative care (27.5 vs 10 months), making it a potentially promising modality in the management of locally advanced ICC.…”
Section: Radiotherapy For Unresectable Cholangiocarcinomamentioning
confidence: 99%